Lime plaster cover of the dead 12, 000 years ago – new evidence for the origins of lime plaster technology. (2019) - Friesem, David E.; Abadi, Itay; Shaham, Dana; Grosman, Leore
Abstract: Abstract: The production of lime plaster is especially important as a technological development in human prehistory as it requires advanced knowledge and skills to transform rocks to a plastic yet durable material. The large-scale production of lime plaster is considered a development of farming societies during the Neolithic period around 10, 000 years ago. To date, the archaeological evidence from the Middle and Late Epipalaeolithic in the southern Levant (c. 17, 000–11, 500 cal BP) indicates that only initial production of partially carbonated lime plaster was performed by Palaeolithic foragers. Our study analysed lime plaster covering burials at a Natufian cemetery in Nahal Ein Gev II, dating to 12, 000 years ago. Using infrared spectroscopy and soil micromorphology we show how this lime plaster is of an unprecedented high quality and we reconstruct its production. The results exhibit a technological leap forward at the end of the Palaeolithic. We provide a new model for understanding the evolutionary paths of lime plaster technology during the Palaeolithic–Neolithic transition.